Citizenship and Belonging in France and North America
XVII, 260 p.
Keywords: The first decades of the new millennium have been marked by major political changes. Although The West has wished to revisit internal and international politics concerning migration policies, refugee status, integration, secularism, and the dismantling of communitarianism, events like the Syrian refugee crisis, the terrorist attacks in France in 2015-2016, and the economic crisis of 2008 have resurrected concepts such as national identity, integration, citizenship and re-shaping state policies in many developed countries. In France and Canada, more recent public elections have brought complex democratic political figures like Emmanuel Macron and Justin Trudeau to the public eye. Both leaders were elected based on their promising political agendas that aimed at bringing their countries into the new millennium; Trudeau promotes multiculturalism, while Macron touts the diverse nation and the inclusion of diverse ethnic communities to the national model. This edited collection aims to establish a dialogue between these two countries and across disciplines in search of such discursive illustrations and opposing discourses. Analyzing the cultural and political tensions between minority groups and the state in light of political events that question ideas of citizenship and belonging to a multicultural nation, the chapters in this volume serve as a testimonial to the multiple views on the political and public perception of multicultural practices and their national and international applicability to our current geopolitical context.